Strategic Water Management in the Great Lakes: Integrating Network Models and Optimization - Liu, Jingpeng; Chen, Qingyun; Lu, Yifan (Transactions on Environment, Energy and Earth Sciences, 2024)
The Great Lakes are the largest freshwater system in the world and have a significant impact on local social development and people’s lives. To address the complex water level management challenges in the North American Great Lakes region, this study develops a network model and optimization algorithm for simulating the dynamics of the Great Lakes and their Atlantic tributaries. This study scientifically determines the optimal water level of the Great Lakes for each month of the year based on multi-objective planning theory, and uses an improved PID algorithm to regulate the dams to maintain the optimal water level, while considering the Great Lakes’ significant economic, ecological, and social values in the context of climate change uncertainty and stakeholder conflict. The study strives to balance these aspects to provide a solid foundation for ecological conservation, economic growth, and climate resilience, as well as a viable strategy for Great Lakes water optimization issues.